Divergent paths : Hegel in Marxism and Engelsism - Levine, Norman, 1931- (Lexington Books, 2006)
Divergent Paths is the first in a series of three volumes that explores the historiography of the relationship between Hegel and Marx; it sets the terms of the relationship between Marx and Engels, and explores the genesis of the theories of Marxism and Engelsism from the late 19th century to the present day. Given the vast pool of contemporary post Marxist theoretical work, a study like this is sorely needed. This is the most thorough exploration of Marx's ideas from Hegel through to the present day and is absolutely essential reading.